1986
DOI: 10.1016/s0022-5347(17)45276-1
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Nephrolithotomy in the Spinal Cord Injury Population

Abstract: We evaluated 23 male spinal cord injury patients who underwent percutaneous nephrolithotomy for the success rate of stone removal and the incidence of operative complications. There were 18 quadriplegic and 5 paraplegic patients, and 5 had bilateral procedures. Of the kidneys 7 had staghorn calculi, 8 had pelvic and caliceal combinations, 6 had large multiple caliceal stones, 4 had large (more than 2.5 cm.) pelvic stones and 3 had pelvic stones less than 2.5 cm. Placement of a nephrostomy tube and stone extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
29
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 8 publications
4
29
0
Order By: Relevance
“…PCNL is the gold standard for stones measuring 2 cm and above in the renal pelvis and this remains the case in patients with SCI. Five published series [26][27][28][29][30] report stone-free rates of around 90%, which at first look appears comparable to the standard PCNL outcomes. (Table 4) However, in the Chicago series all patients had a second-look PCNL as standard, and only 19 renal units were stone free after first PCNL in the UK series.…”
Section: Ureteroscopicmentioning
confidence: 70%
See 1 more Smart Citation
“…PCNL is the gold standard for stones measuring 2 cm and above in the renal pelvis and this remains the case in patients with SCI. Five published series [26][27][28][29][30] report stone-free rates of around 90%, which at first look appears comparable to the standard PCNL outcomes. (Table 4) However, in the Chicago series all patients had a second-look PCNL as standard, and only 19 renal units were stone free after first PCNL in the UK series.…”
Section: Ureteroscopicmentioning
confidence: 70%
“…28,30 In the earliest study from 1986, there was an average of 2.04 procedures per patient. 26 In this respect, PCNL in patients with SCI is a more complex and significantly undertaking, often requiring multiple procedures to achieve stone clearance. In the major part of the more contemporary series, 13 out of the 54 procedures required multiple punctures and 23 punctures were supracostal.…”
Section: Ureteroscopicmentioning
confidence: 99%
“…Furthermore, Lechevallier et al [13] reported a higher likelihood for renal scar formation after ESWL sessions than after percutaneous nephrolithotomy [13]. Therefore, treatment options were directed towards a percutaneous surgical approach [14][15][16][17], open surgical approach [18], or various combinations of multi-modality treatments [8,19,20]. The decision to perform percutaneous nephrolithotomy in our patient rather than open surgery was influenced by a variety of factors.…”
Section: Discussionmentioning
confidence: 85%
“…2,4,5 In the SCI population, average clearance rates using SWL are 44-55%, [9][10][11] and percutaneous nephrolithotripsy clearance rates are 54-87%. 12,13 One possible explanation for the high failure rate of URS in the SCI population may be that chronic neurogenic bladder dysfunction can cause fibrosis and bladder wall contractures which alter the ureteral orifice and urethral anatomy. 14 In addition, patients with SCI often suffer from lower extremity contractures making positioning in the lithotomy position difficult or impossible.…”
Section: Discussionmentioning
confidence: 99%